Using surveys of business perceptions as a guide to growth-enhancing fiscal reforms - Florian Misch; Norman Gemmell; Richard Kneller (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2013)
This paper assesses the merits of using surveys of business perceptions of growth constraints as a guide to growth-enhancing fiscal policy reforms. Using endogenous growth models in which the government levies an income tax to provide public inputs to the production of private firms, the paper demonstrates that business perceptions of growth constraints are subject to systematic biases except when firms compare different types of public services or different types of public capital. In particular firms can be expected to systematically over-estimate the growth-enhancing effects of lower tax rates, and under-estimate the growth-enhancing effects of greater provision of public capital. It is then shown that these theoretical predictions regarding how firms rank constraints correspond closely to the observed ranking of constraints by firms in the World Bank's Enterprise Surveys.
Keywords: D20; E62; O12; 330; Economic Growth; Fiscal Policy; Imperfectly Informed Governments; Business Perceptions; Diagnostics; Subjective Data